Overcoming One-way Impact Evaluation of Rural Electrification Projects - Groth, Annika (International Journal of Energy Economics and Policy, 2020)
Impact evaluation in rural electrification research usually studies the effects under the framework of a one-dimensional approach from electrification to socio-economic development and/or vice versa. Recent research identifies the need for more research uncovering reverse feedback and complexities of rural electrification projects. For planners, regulators and investors, it is very important to know about the dynamics to facilitate their planning. This paper assesses effects of electrification on daily lighting, lumen and operating hours of micro enterprises. It is based on a case study of a with the main grid interconnected mini-grid project located in Southern Tanzania. Propensity Score Matching Method is applied to identify control and research groups. Furthermore, qualitative data allows for a comprehensive overview on dynamic interactions between electricity demand and the local market structure. The study reveals that mini-grid-electricity has significant impacts on the quality of illumination in micro enterprises, but no evidence of impacts on lighting and operation hours can be identified. Off-grid systems, mainly consisting of solar technologies, might already meet a major share of electricity demand and do not necessarily have to compete with grid power supply, but can complement it. Complementary activities and infrastructures are needed to stimulate electricity demand and business development. Keywords: Rural electrification; impact evaluation, propensity score matching, micro enterprises, Sub-Saharan Africa JEL Classifications: C21, I32, O12, Q42 DOI: https://doi.org/10.32479/ijeep.8941